PICO: What it is and what it is not. (October 2021) - Schiavenato, Martin; Chu, Frances
Abstract: Aim: To assess the role and effectiveness of the mnemonic PICO (Population, Intervention, Comparator and Outcome) in evidence-based practice (EBP) pedagogy. Background: The mnemonic "PICO" is a well-established tool in nursing EBP pedagogy. Nevertheless, application of this tool in nursing curricula is not currently supported by evidence of its effectiveness. Further, there are reports that PICO as a tool is unhelpful in the classroom. Design/Methods: We reviewed the literature on PICO; specifically, the mnemonic's origin, purpose, and effectiveness in practice. Results: Our analysis reveals that PICO is limited in terms of its effectiveness and scope of inquiry. Conclusion: A reevaluation of PICO's role in nursing pedagogy is essential. To start, we propose a de-emphasis on PICO as an exclusive or preferred tool, and an emphasis on critical evaluation of the literature, and the whole of the EBP process. We propose a search for more effective methods to improve matching native clinical questions to the retrieval of data that informs patient care.